2007
DOI: 10.1177/104063870701900212
|View full text |Cite
|
Sign up to set email alerts
|

Muscular Pseudohypertrophy (Steatosis) in a Bovine Fetus

Abstract: Abstract. Muscular pseudohypertrophy was diagnosed in the cervical musculature of a full-term crossbred Simmental fetus delivered by fetotomy. Only head and cervical regions were submitted for pathologic examination; the rest of the fetal body was reportedly normal. The neck musculature of the fetus was markedly deformed by 23 cm and 18 cm in diameter, firm, spherical masses that consisted of enlarged and pale left splenius and right serratus ventralis cervicis muscle, respectively, covered by intact skin. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In the present case, excessive pseudo-hypertrophy of left splenius, left and right serratuscervicis, brachiocephalicus, and pectoral muscles were observed, while supraspinatus, trapazius, omotransversarius, deltoideus and part of triceps were remarkably either enlarged or atrophied. Gross and histological findings were similar to Langohr et al (2007), and they opined that muscle severity and selective involvement are always associated with a lack of innervation or denervation of affected muscles due to the cervical spinal cord deformation. If the denervation is permanent, it leads to atrophy of the respective muscle.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In the present case, excessive pseudo-hypertrophy of left splenius, left and right serratuscervicis, brachiocephalicus, and pectoral muscles were observed, while supraspinatus, trapazius, omotransversarius, deltoideus and part of triceps were remarkably either enlarged or atrophied. Gross and histological findings were similar to Langohr et al (2007), and they opined that muscle severity and selective involvement are always associated with a lack of innervation or denervation of affected muscles due to the cervical spinal cord deformation. If the denervation is permanent, it leads to atrophy of the respective muscle.…”
Section: Discussionmentioning
confidence: 70%
“…The muscular pseudo-hypertrophy involves various cervical and shoulder muscles, either unilaterally or bilaterally. Langohr et al (2007) and Ghuman et al (2012) reported the pseudo-hypertrophy of the left splenius and right serratusventraliscervicis, while Singh et al (2017) reported the hypertrophy of brachiocephalicus, trapazius, sternocephalicus, and serratuscervicis muscles. In the present case, excessive pseudo-hypertrophy of left splenius, left and right serratuscervicis, brachiocephalicus, and pectoral muscles were observed, while supraspinatus, trapazius, omotransversarius, deltoideus and part of triceps were remarkably either enlarged or atrophied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation